2005
DOI: 10.1016/j.schres.2004.09.013
|View full text |Cite
|
Sign up to set email alerts
|

A comparative profile analysis of neuropsychological function in men and women with schizotypal personality disorder

Abstract: The purpose of this study was to compare the cognitive profiles of men and women with clinically defined schizotypal personality disorder (SPD). We examined the neuropsychological profile of SPD in 26 right-handed females and 31 right-handed males who met DSM-IV criteria for SPD, and matched comparison subjects. Cognitive performance was assessed on measures of abstraction, verbal and spatial intelligence, learning and memory, language, attention, and motor skills. Neuropsychological profiles were constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…For example, neuroimaging studies of the caudate nucleus have reported relatively larger caudate volume (Filipek et al 1994;Goldstein et al 2001;Murphy et al 1996) and higher caudate presynaptic dopamine synthesis capacity (Laakso et al 2002) in healthy women compared with healthy men. Moreover, Voglmaier et al (2005) reported that, compared with male SPD subjects, female SPD subjects showed less verbal learning deficits, which is in accord with findings in schizophrenia (Goldstein et al 1998). Studies of gender difference in schizophrenia also have suggested that female schizophrenic patients are prone to show more positive and fewer negative symptoms and a better response to neuroleptics (Goldstein and Levine 2000;Tamminga 1997), suggesting that gender might have an effect on cognitive and clinical symptoms (Davatzikos and Resnick 1998) in SPD or schizophrenia.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…For example, neuroimaging studies of the caudate nucleus have reported relatively larger caudate volume (Filipek et al 1994;Goldstein et al 2001;Murphy et al 1996) and higher caudate presynaptic dopamine synthesis capacity (Laakso et al 2002) in healthy women compared with healthy men. Moreover, Voglmaier et al (2005) reported that, compared with male SPD subjects, female SPD subjects showed less verbal learning deficits, which is in accord with findings in schizophrenia (Goldstein et al 1998). Studies of gender difference in schizophrenia also have suggested that female schizophrenic patients are prone to show more positive and fewer negative symptoms and a better response to neuroleptics (Goldstein and Levine 2000;Tamminga 1997), suggesting that gender might have an effect on cognitive and clinical symptoms (Davatzikos and Resnick 1998) in SPD or schizophrenia.…”
mentioning
confidence: 60%
“…Previous research by our group had shown that the neuropsychological deficits in female SPD subjects exist, though they differ from those in male subjects. For example, female SPD subjects showed abnormal verbal learning on the California Verbal Learning Test, but these deficits were less severe than those found in male SPD subjects (Voglmaier et al 2005). Nonetheless, given that executive functioning can be adversely affected by caudate nucleus lesions, given the anatomical connections with the DLPFC (see above) and that such disturbances might impact on verbal learning, we thought it important to test whether neuroleptic-naïve female SPD subjects would similarly show abnormalities in the caudate nucleus, as we previously showed in male SPD subjects (Levitt et al 2002).…”
mentioning
confidence: 79%
“…Their deficits include abnormal performance on delayed-response tasks (Park and Holzman, 1992; Goldman-Rakic, 1994; Glahn et al, 2003; Park et al, 2003; Saperstein et al, 2006; Genderson et al, 2007), figure search (Longevialle-Henin et al, 2005), mental rotation (de Vignemont et al, 2006; Halari et al, 2006), Gestalt perception (O'Donnell et al, 1996; Parnas et al, 2001; Cavezian et al, 2007; Kimhy et al, 2007), spatial span (Cannon et al, 2000; Perry et al, 2001; Manoach et al, 2005; Genderson et al, 2007; Thoma et al, 2007), 3-D real-world navigation Daniel et al (2007), and referencing (Landgraf et al, 2010a; Mazhari et al, 2010). According to a meta-analysis, there is an overall effect size of −1.00 regarding VS working memory deficits in chronic schizophrenia patients (Piskulic et al, 2007), and these deficits are independent of gender differences (Albus et al, 1997; Reichenberg et al, 2002; Voglmaier et al, 2005; Halari et al, 2006; Wolitzky et al, 2006). Hence, visual information processing appears to be deteriorated in schizophrenia, increases with the progression of the disease, and is related to basic visual acquisition.…”
Section: The Vision Perspective On Schizophreniamentioning
confidence: 99%
“…Verbal learning was assessed using the California Verbal Learning Test (CVLT), total words learned trials 1-5 (Delis et al, 1987). This test was selected as a test of verbal working memory and because it has been shown by our laboratory to be abnormal in SPD subjects (Voglmaier et al, 1997;Voglmaier et al, 2000;Voglmaier et al, 2005).…”
Section: Clinical Measuresmentioning
confidence: 99%